Predictors of Success in Horizontal Strabismus Surgery: Insights from a Prospective Study - Tjujitno, Aurellia Valmai; Prastyani, Reni; Susanto, Joni; Loebis, Rozalina; Indriaswati, Luki; Wulandari, Lely Retno (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2025)
Highlights: The younger age and shorter duration of misalignment are significant predictors of success in horizontal strabismus surgery. Younger patients tend to have higher success rates, and shorter durations of misalignment correlate with better surgical outcomes. Despite variations in population and surgical methods, the overall success rate of 82.3% for horizontal strabismus surgeries aligns with previous studies. This consistency underscores the reliability of surgical outcomes in different settings.   Abstract Introduction: Strabismus is an eye disorder characterized by misalignment of the eyes, which can occur in individuals of any age. This study explored the surgical outcomes of horizontal strabismus correction in patients, aiming to provide insights into the factors influencing success. Methods: A prospective study was conducted with 17 patients (n=17) who underwent surgery at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia. Preoperative factors, including age, duration of misalignment, and preoperative angle of strabismus, were analyzed for their impact on surgical success. The International Business Machines Corporation (IBM) Statistical Package for the Social Sciences (SPSS) for Macintosh version 27.0 was used for data analysis. Results: This study reviewed the medical records of 17 research samples (n=17). A significant change in the median angle of deviation prism diopters (PD) preoperatively was indicated by the median Postoperative Deviation (PD) (p<0.001). A significant difference in median age at surgery was observed between successful and unsuccessful cases (p=0.035), with younger individuals exhibiting a higher success rate. The duration of misalignment emerged as a crucial factor, with a shorter duration correlating positively with a higher probability of surgical success (p<0.001). Notably, successful outcomes were achieved by all children (100%), suggesting a potential trend indicating age as a predictor of success. While the preoperative angle of strabismus did not significantly impact success, a trend emerged (p=1), indicating a potential threshold effect for more significant angles. Conclusion: Knowing the significance of age and duration of misalignment on the success rate of strabismus surgery allows for enhanced preoperative assessments, optimized timing of surgery, and developed predictive models to assist in clinical decision-making, ultimately leading to more efficient and successful surgical outcomes.